Real exchange rate decompositions - Bruno Feunou; Jean-Sébastien Fontaine; Ingomar Krohn (Bank of Canada, 2022)
We provide a novel daily decomposition of the real exchange rate that exploits a direct link between bond and foreign exchange (FX) markets. Real exchange rate dynamics can be attributed to changes in the expected future level of the exchange rate; cross-country differentials of expected inflation, yields and bond term premia; and an FX risk premium. Through a variance decomposition exercise, we find that the FX risk premium is the dominant component. Monetary policies and macroeconomic news announcements largely move the real exchange through changes in the FX risk premium.
Keywords: E43; F31; G12; 330; Asset pricing; Exchange rates; International financial markets; Monetary policy transmission